2x+10+x+7=x*x+12x+35

Simple and best practice solution for 2x+10+x+7=x*x+12x+35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+10+x+7=x*x+12x+35 equation:


Simplifying
2x + 10 + x + 7 = x * x + 12x + 35

Reorder the terms:
10 + 7 + 2x + x = x * x + 12x + 35

Combine like terms: 10 + 7 = 17
17 + 2x + x = x * x + 12x + 35

Combine like terms: 2x + x = 3x
17 + 3x = x * x + 12x + 35

Multiply x * x
17 + 3x = x2 + 12x + 35

Reorder the terms:
17 + 3x = 35 + 12x + x2

Solving
17 + 3x = 35 + 12x + x2

Solving for variable 'x'.

Reorder the terms:
17 + -35 + 3x + -12x + -1x2 = 35 + 12x + x2 + -35 + -12x + -1x2

Combine like terms: 17 + -35 = -18
-18 + 3x + -12x + -1x2 = 35 + 12x + x2 + -35 + -12x + -1x2

Combine like terms: 3x + -12x = -9x
-18 + -9x + -1x2 = 35 + 12x + x2 + -35 + -12x + -1x2

Reorder the terms:
-18 + -9x + -1x2 = 35 + -35 + 12x + -12x + x2 + -1x2

Combine like terms: 35 + -35 = 0
-18 + -9x + -1x2 = 0 + 12x + -12x + x2 + -1x2
-18 + -9x + -1x2 = 12x + -12x + x2 + -1x2

Combine like terms: 12x + -12x = 0
-18 + -9x + -1x2 = 0 + x2 + -1x2
-18 + -9x + -1x2 = x2 + -1x2

Combine like terms: x2 + -1x2 = 0
-18 + -9x + -1x2 = 0

Factor out the Greatest Common Factor (GCF), '-1'.
-1(18 + 9x + x2) = 0

Factor a trinomial.
-1((6 + x)(3 + x)) = 0

Ignore the factor -1.

Subproblem 1

Set the factor '(6 + x)' equal to zero and attempt to solve: Simplifying 6 + x = 0 Solving 6 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + x = 0 + -6 x = 0 + -6 Combine like terms: 0 + -6 = -6 x = -6 Simplifying x = -6

Subproblem 2

Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3

Solution

x = {-6, -3}

See similar equations:

| 1.2x+5=7 | | 4x(x-2)=5 | | y/7=3/14 | | =4x^3y^5 | | 4d-2=6 | | (4x-2)+(6x+6)+(7x-18)=360 | | -45=15x | | -7x-8y=-19 | | -3=-r | | 130-6x=30x+18 | | -3x-7y=-14 | | 82-6x=39x+17 | | 3x+2+3x+4=-24 | | 3+8(m-6)= | | 8-9x=131-30x | | 135-7X=38X+20 | | x+98+44=180 | | 11-10x=131-38x | | x+96+47=180 | | 4(x-1)=x+20 | | 3y+2x=5-x | | E^3x+2=9 | | 7-7X=106-28X | | (6a+10)=(3a+55) | | 16x-8+27x-72=-1134 | | 2-8n+3n=17-95 | | -t-26+4t=9t-8 | | 1-4x=10+5x | | 4(c-3)=5(c-8) | | LNX=2 | | x+5-6x=5 | | 7x+9y=-14 |

Equations solver categories